2011
DOI: 10.1523/jneurosci.0182-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Photopigment Is Enhanced in Mouse Cone Photoreceptors Expressing RPE65 Protein

Abstract: As cone photoreceptors mediate vision in bright light, their photopigments are bleached at a rapid rate and require substantial recycling of the chromophore 11-cis retinal (RAL) for continued function. The retinal pigment epithelium (RPE) supplies 11-cis RAL to both rod and cone photoreceptors; however, stringent demands imposed by the function of cones in bright light exceed the output from this source. Recent evidence has suggested that cones may be able to satisfy this demand through privileged access to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 39 publications
3
35
0
Order By: Relevance
“…To investigate if RPE65 is localized within human cones, two polyclonal antibodies raised against distinct epitopes of RPE65 were used that have been previously shown to exhibit high specificity in mouse (Redmond and Hamel, 2000; Tang et al, 2011) and chicken (Moiseyev et al, 2008) (see Table 1). We evaluated the specificities of both antibodies for human RPE65 in the RPE, as this is the region of the eye where the protein is widely accepted to be localized and to function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate if RPE65 is localized within human cones, two polyclonal antibodies raised against distinct epitopes of RPE65 were used that have been previously shown to exhibit high specificity in mouse (Redmond and Hamel, 2000; Tang et al, 2011) and chicken (Moiseyev et al, 2008) (see Table 1). We evaluated the specificities of both antibodies for human RPE65 in the RPE, as this is the region of the eye where the protein is widely accepted to be localized and to function.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence first arose from the discovery of mRNA in salamander cones (Ma et al, 1998) and the protein in mammalian cones through immunohistochemistry (IHC) (Znoiko et al, 2002). We recently localized RPE65 to the outer segment (OS) region of the mouse cone and found that mouse strains with lower amounts of cone RPE65 were less efficient at regenerating cone photopigment than those with higher levels (Tang et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…These antibodies were affinity-purified prior to use by Protein Purify Ltd. The primary antibodies used in this study included guinea pig anti-chick Opn5m antibody (7) and rabbit anti-RPE65 anti-body (a gift from Dr. Rosalie K. Crouch, Medical University of South Carolina) (15). We performed Western blotting analysis using the antibodies and confirmed that the anti-mouse and human/monkey Opn5m antibodies recognized the recombinant proteins of full-length mouse and human Opn5m expressed in HEK293 cells, respectively (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…8); furthermore, many remaining cones are not functional at that age in Rpe65 À/À mice, although they can be restored to activity by reintroduction of 11-cis-retinal. 55 The source and identity of chromophore for rod photoreceptors in T À/À mice, though, is unclear at this time. However, Rpe65 À/À mice may generate and utilize 9-cis-retinal to form isorhodopsin.…”
mentioning
confidence: 99%